No bad parts : healing trauma & restoring wholeness with the internal family systems model - Schwartz, Richard C. (Sounds True, 2021)
"Dr. Schwartz is the creator of Internal Family Systems (IFS), a paradigm-changing model of consciousness that has been transforming psychology for decades. Here, you'll learn why IFS has been so effective in areas such as trauma recovery, addiction therapy, depression, and more. IFS overturns the idea that we have one "true" identity and recognizes that having multiple parts is not a pathology, but a normal and healthy function of the human mind. Dr. Schwartz shares insights and practices to help you recognize your own "inner family" of parts, understand how each part seeks to help and protect you even when it seems problematic, engage in inner dialogue to restore balance and self-love-and deepen your awareness of the higher Self that holds and encompasses every facet of your diverse consciousness"--